AIR POLLUTION TOLERANCE INDEX OF SOME SELECTED GYMNOSPERM SPECIES ALONG THE ROAD SIDE OF KATHMANDU VALLEY, NEPAL - Hamal, Jaya Prakash; Chettri, Mukesh Kumar (Ecoprint: An International Journal of Ecology, 2017)
Response of plants towards air pollution is assessed by air pollution tolerance index (APTI). Four species of Gymnosperms (Thuja orientiales, Cedrus deodara, Pinus roxburghii and Araucaria bidwillii) were evaluated for APTI. Leaves were collected during winter season from polluted sites (Airport, Dhumbarahi, Jawalakhel, Ratnapark, and Sankhapark) and less polluted site (Narayanthan) of Kathmandu valley. Of four gymnosperm species collected from road side, all species (Cedrus deodara, Araucaria bidwillii, Thuja orientiales and Pinus roxburghii) showed high value of APTI (i.e., more than 8), indicating their resistance to air pollution. ECOPRINT 24: 13-19, 2017